The Use of Blended Learning through the Lerne Deutsch mit Dani Website for Listening Skill - Dina Tri Lestari; Herri Akhmad Bukhori (Universitas Negeri Malang, 2025)
This study aims to describe the use of blended learning through the Lerne Deutsch mit Dani website for listening skill and find out students’ opinions on its application. This type of research uses a descriptive qualitative approach with the subject of 32 students of class XI-4 SMA Negeri 7 Malang. Data in this study were obtained through observation and questionnaire sheets. Observation data describe how the Lerne Deutsch mit Dani website supports listening skills in German language learning through blended learning, while the questionnaire data is used to find out students’ opinions. The observation results show that students are able to understand the audio and follow the learning stages which include the opening, main, and closing activities. The questionnaire results state that the application can train listening skills and make learning more interesting. Based on the results of this study, it can be concluded that the use of blended learning through the Lerne Deutsch mit Dani website for listening skill gets a positive response.